PERAN SISTEM PERTANIAN LOKAL DALAM MEKANISME PEMENUHAN KEBUTUHAN PANGAN (FOOD COPING STRATEGY ) MASYARAKAT ADAT KASEPUHAN CICARUCUB BERBASIS KEARIFAN LOKAL - siti Widiati; Rusmana Rusmana; Mirajiani Mirajiani (JURNAL AGRIBISNIS TERPADU, 2020)
The Kasepuhan Cicarucub Indigenous farming system based on local wisdom, can play a role in the mechanism of meeting household food needs (Food Coping Strategy, the Indigenous People of Kasepuhan Cicarucub, Level I. in general, the food coping strategy at Stage I, namely 1) looking for other work, 2) changing food, 3) adding access to immediately get food, 4) doing changes in food distribution and frequency. Food Coping Strategy Kasepuhan Cicarucub Indigenous Peoples are at Level I, these conditions indicate that the mechanism of household survival in meeting food needs, including food security. Because the mechanism of food fulfillment at the household level of the Kasepuhan Cicarucub Indigenous Peoples does not take drastic steps, such as the mechanism of defending the behavior found in nerves II or III. The behavior of food coping strategy is done differently according to the problems faced by it. More and more households are taking drastic steps such as behavior at Levels II and III, showing a household that cannot stand food. This is due to a decrease in production, income to food consumption and nutritional status influenced by factors, such as.